Survei Pukulan Short Servis Backhand Bulutangkis pada PB Talenta Kabupaten Kebumen Jawa Tengah : Penelitian - Mokhamad Parmadi; Fia Adinda Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mastery of basic service techniques in badminton has a very important role, because service has a very big influence in getting points and winning the match. The purpose of this study was to determine the level of backhand short serve ability in badminton in PB Talenta Kebumen athletes. This study is a descriptive quantitative percentage study using a test instrument in the form of a backhand short serve test. The population in this study were 50 active members of PB Talenta. The sample selection in this study used a purposive sampling technique. The sample used by researchers in this study consisted of 10 athletes who met the research criteria. The results of the study showed the category